Peningkatan Pemahaman Peserta Didik SMA IT Harapan Bunda Semarang Mengenai Merek Usaha - Khaidar Alifika El Ula; Endah Pujiastuti; Subaidah Ratna Juita (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2023)
The budding entrepreneurship that many students are starting to do often does not have the right business brand. In fact, brands are the spirit of the business world so that it runs smoothly, especially for goods and/or services. One of the first things that novice entrepreneurs must do when starting their business is to design a brand that is appropriate and reflects the spirit of their business. Designing a business brand by combining the strongest characteristics of the business and making it attractive to target consumers is an invaluable added value. Therefore, it is necessary to increase legal understanding for prospective entrepreneurs when starting their business, especially in the field of branding. The goal to be achieved is: to provide an understanding of the importance of business branding. This service is carried out using direct lecture and question and answer methods, and evaluation is carried out by comparing the results of distributing pre-test and post-test questionnaires to increase student understanding.